Youth Empowerment Through Digital Marketing for UMKM Development in Ponggok Village, Mojo District, Kediri Regency - Qolbin Salim; Wan Maina Sela; Syi'inatul Cholifah; Shofia Chafi Azka Haq; Muhammad Balya Aminudin; Fina Rohmatul Ummah; Jeihan Ali Azhar; Binti Mutafarida (FEBI UIN Sunan Kalijaga Yogyakarta, 2025)
This community service program aims to empower the youth of Ponggok Village, Mojo District, Kediri Regency through digital marketing to enhance the development of local Micro, Small, and Medium Enterprises (MSMEs). The program utilizes an Asset-Based Community Development (ABCD) approach, which includes five phases: Discovery, Dream, Design, Define, and Destiny. The main focus is on equipping the youth with the skills necessary to utilize social media platforms like TikTok, Facebook, and Instagram for promoting MSME products. The results show a significant improvement in the digital marketing capabilities of the participating youth and MSME owners, leading to broader and more effective product promotion. This initiative not only empowers the youth but also contributes to the overall economic development of the community. The findings suggest that ongoing support and potential certification, such as halal and BPOM, could further enhance the product quality and market reach of local MSMEs.